The Antarctic Treaty system: what's on the horizon? - Julia Jabour (2012)
Antarctic commentary is usually full of superlatives when describing so years of the Antarctic Treaty and the subsequent system that was developed by its Parties. Primarily this is because the Antarctic Treaty itself has lasted so long, and appears to be robust and enduring. This short paper looks at what is on the horizon for the Parties to the various instruments of the Antarctic Treaty System - the Antarctic Treaty and its Protocol on Environmental Protection, and the Convention on the Conservation of Antarctic Marine Living Resources. It identifies a number of key areas of concern that will challenge the Parties' ability to maintain the successful status quo of today and meet the future with confidence. The future, characterised by the changing climate, will test the Parties in a number of crucial ways, including bringing into question their long-held principles of diplomacy and consensus decision-making.